2020
DOI: 10.51352/jim.v5i2.247
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Demam Berdarah Dengue (DBD) adalah penyakit demam akut yang disebabkan oleh virus dengue yang masuk ke peredaran darah manusia melalui gigitan nyamuk dari genus Aedes. Sampai saat ini belum ada obat untuk menyembuhkan penyakit DBD, sehingga masyarakat sering panik jika tertular virus dengue. Berbagai cara dilakukan untuk mencegah penularan virus dengue salah satunya adalah dengan penggunaan tanaman sebagai anti nyamuk alami. Penggunaan bahan kimia secara terus menerus, selain berdampak buruk terhadap kesehatan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The research results showed that at a concentration of 5%, lemon peel extract had repellent power against the Aedes aegypti mosquito. Further studies by [7] regarding the effectiveness of lime peel extract on mosquito protection showed that the higher the concentration of essential oils derived from lime peel extract, the more effective it was on mosquito protection, up to 98% concentration. 45% for 8 hours.…”
Section: Introductionmentioning
confidence: 99%
“…The research results showed that at a concentration of 5%, lemon peel extract had repellent power against the Aedes aegypti mosquito. Further studies by [7] regarding the effectiveness of lime peel extract on mosquito protection showed that the higher the concentration of essential oils derived from lime peel extract, the more effective it was on mosquito protection, up to 98% concentration. 45% for 8 hours.…”
Section: Introductionmentioning
confidence: 99%